Orkestra sebagai Peristiwa Mediasi: Jakarta City Philharmonic, Tubuh dan Materialitas - Fisandra, Halida Bunga; Danusiri, Aryo (Resital: Jurnal Seni Pertunjukan, 2022)
The Covid-19 virus has infiltrated the recesses of human life around the world. The phenomenon that arises from restrictions on movement in offline spaces is the massive effort by humans to adapt to online media. We can see many artists and musicians performing through various digital platforms, including the Jakarta City Philharmonic (JCP) orchestra. This article will describe the changing process of orchestral space-time in online media which has eliminated bodily interactions as an essential element in musical performances. Through contemporary anthropology, we argue that technology allows orchestras to exist as mediating events through their role as mediators; which reassembles the connections and negotiations between the body and the materiality of the orchestra. The virtual ethnographic method was used through online observations and in-depth interviews with artistic directors, assistant musicians, and orchestra musicians. The results showed that the JCP orchestra experienced an embodied experience arising from technological disassembly and reassembly as a connecting tissue. It can be seen from the relation between actants, and their implications for evaluating artistic values and performativity of orchestral performances.